2007
DOI: 10.1029/2006jg000308
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical water extraction of amino acids from Atacama Desert soils

Abstract: [1] Amino acids are considered organic molecular indicators in the search for extant and extinct life in the Solar System. Extraction of these molecules from a particulate solid matrix, such as Martian regolith, will be critical to their in situ detection and analysis. The goals of this study were to optimize a laboratory amino acid extraction protocol by quantitatively measuring the yields of extracted amino acids as a function of liquid water temperature and sample extraction time and to compare the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 54 publications
4
55
0
Order By: Relevance
“…Even if it has been repeatedly observed that bioactive extracts might be obtained at high temperatures (maintaining the solvent's liquid state), this parameter should be studied and selected for each type of matrix/bioactive being extracted. On the other hand, possible formation of new components in the extracts, as a result of the occurrence of different reaction during the extraction process, has to be considered [73,74]. This point, that is clear shortcoming when the natural composition of a sample is sought, has been considered by some authors as an additional advantage in terms of bioactivity of the achieved extracts [75].…”
Section: Methodological and Technological Advancesmentioning
confidence: 99%
“…Even if it has been repeatedly observed that bioactive extracts might be obtained at high temperatures (maintaining the solvent's liquid state), this parameter should be studied and selected for each type of matrix/bioactive being extracted. On the other hand, possible formation of new components in the extracts, as a result of the occurrence of different reaction during the extraction process, has to be considered [73,74]. This point, that is clear shortcoming when the natural composition of a sample is sought, has been considered by some authors as an additional advantage in terms of bioactivity of the achieved extracts [75].…”
Section: Methodological and Technological Advancesmentioning
confidence: 99%
“…The Yungay (Chile) and Arequipa (Peru) regions of the Atacama Desert are the driest hot places on Earth, serving as a compositional Martian analogue because of its sulphate and perchlorate mineralogy and low organic content (Catling et al 2010;Peeters et al 2009;Buch et al 2006;Amashukeli et al 2007;Meunier et al 2007;Skelley et al 2007). This is suggested to be the result of the highly oxidizing composition of the Atacama Desert soil (Sutter et al 2005;Ewing et al 2006;Navarro-González et al 2003;Lester et al 2007).…”
Section: Atacama Desertmentioning
confidence: 99%
“…The analysis via the optimized protocol, however, allowed for identification of several amino acids and quantitation of total amino acid content at 450 mM. This result is a significant advance in the MOA capabilities because it demonstrates the potential for the direct analysis of aqueous extracts without extensive preprocessing (Kminek et al, 2000;Amashukeli et al, 2007).…”
mentioning
confidence: 98%